Local Activation of the Alternative Pathway of Complement System in Mycotic Keratitis Patient Tear - Shait Mohammed, Mohammed Razeeth; Krishnan, Sandhya; Amrathlal, Rabbind Singh; Jayapal, Jeya Maheshwari; Namperumalsamy, Venkatesh Prajna; Prajna, Lalitha; Kuppamuthu, Dharmalingam (Frontiers in Cellular and Infection Microbiology, 2020)
Aspergillus flavus and Fusarium solani are the predominant causative agents of mycotic keratitis in the tropical part of the world. Tear proteins play a major role in the innate immune response against fungal infection as has been shown by the presence of complement proteins and neutrophil extracellular trap proteins in keratitis patient tear. In this study, we examined the presence of the components of the alternate pathway of complement system and their functional state in the tear film of mycotic keratitis patients. Complement proteins namely, C3 and CFH were found only in the open-eye tear of patients but not in control individuals. In vitro analysis showed binding of purified C3b and CFH to fungal spores, which confirmed that the spores can provide a foreign surface for forming complement complex. Analysis of spore bound tear proteins by mass spectrometry showed the presence of known proteins of alternate pathway complement cascade in keratitis patient tear. Hemolytic assay using rabbit RBC confirmed the presence of functional alternate pathway of complement cascade in patient tear, though at a much lower level compared to serum. Presence of negative regulators, CFH and CFI, in patient tear indicate that the complement activity is tightly regulated in fungal infection. Regulation of complement activity is apparentlt at multiple levels in patients since vitronectin and clusterin, two known Membrane Attack Complex (MAC) inhibitors, are also in patient tear. These results imply that the complement system can be modulated from damaging host, however, down regulation of complement might lead to exacerbation of infection. This is the first report in which we have demonstrated the formation and regulation of functional peripheral complement system in fungal keratitis patient tear.